Studi Optimasi Distribusi Air di Daerah Irigasi Manikin, Kabupaten Kupang, Menggunakan Program Dinamik - Robertus Tegar Kurnia Kharistanto; Lily Montarcih Limantara; Anggara Wiyono Wit Saputra; Mokhamad Rusdha Maulana (Postgraduate, University of Mataram, 2025)
This study aims to optimize water distribution in the Manikin Irrigation Area, Kupang Regency (200.98 ha), using deterministic dynamic programming to enhance irrigation efficiency and agricultural productivity. The cropping pattern follows a rice–rice–fallow system, wherein rice is cultivated in the first two seasons and land is left fallow in the third. Data used includes rainfall (2014–2023), irrigation discharge, crop water requirements, climatological parameters, and economic variables. The model maximizes profit as the objective function while considering three constraints: water availability, land area per season, and land area per irrigation stage. The study divides the irrigation network into eight stages and applies forward recursive and backtracking procedures to determine optimal water allocation. Before optimization, only 90 ha (44.78%) were irrigated in the first season and 170 ha (84.59%) in the second. After optimization, coverage increased to 190.23 ha (94.65%) and 200.98 ha (100%), respectively. Corresponding profits rose by 117% in the first season and 18% in the second. These results demonstrate that dynamic programming effectively improves water use efficiency and land productivity in water-limited agricultural systems.